Innovating 3D visualisation for quantum mechanics on the Voxon VX1 volumetric display: techniques and applications - Liew, Zachary Zhe Xi (Nanyang Technological University, 2024)
This report details the utilisation of the Voxon VX1, a cutting-edge 3D volumetric visualisation technology, to display the (time-varying) probability density functions of quantum particles in different potentials, systems and barriers. The primary objective of this project is to craft simple, dynamic representations of probability density functions in 3D to assist students in visualising the mathematical underpinnings behind Quantum Mechanics. The focal animations depict a propagating Gaussian wave packet, which models a free quantum particle across both two-dimensional and three-dimensional space. Various potentials and barriers are then integrated into the numerical simulations to model the dynamics and interaction of the wave packet with the potentials. The numerical data for the time-varying quantum systems are computationally generated using the Split-Step Fourier method. The data is then post-processed in Blender to generate `.obj' files for display on the Voxon VX1 machine utilising its native three-dimensional media player, `VoxieOS'. This report chronicles the progress of the post-processing methods in a timeline format, reflecting tests and modifications leading to the refinement of the animation production methodology. The animations produced by the finalised post-processing techniques provide a straightforward medium to visualise the intricate mathematics behind the probability density functions. Additionally, the 3D Hydrogen probability density functions are also calculated and visualised on the VX1, allowing viewing from varying polar and azimuthal angles. Potential further work is also discussed, including animating the transition of the Hydrogen atom between different energy levels.